Wild reindeer in Norway – population ecology, management and harvest - Reimers, Eigil (Rangifer, 2007)
Wild reindeer in Norway, presently (winter 2005-06) numbering some 25 000 animals, are found in 23 more or less separated areas in the mountainous southern part of the country (see map in appendix). All herds are hunted and management is organized in close cooperation between owner organizations and state agencies. I will provide a historical review of the wild reindeer management and research in Norway and conclude with the present situation. We identify 3 types of wild reindeer on basis of their origin: (1) the original wild reindeer with minor influence from previous domestic reindeer herding activities (Snøhetta, Rondane and Sølenkletten), (2) wild reindeer with some influx of animals from past domestic reindeer herding in the area (Nordfjella, Hardangervidda, Setesdal-Ryfylke) and (3) feral reindeer with a domesticated origin (reindeer released or escaped from past reindeer husbandry units; Forolhogna, Ottadalen North and Ottadalen South, Norefjell-Reinsjøfjell and several smaller areas). In Norway, genetic origin (wild or domesticated), body size and reproductive performance of reindeer differ among areas. Feral reindeer have higher body weights and enjoy higher reproductive rates than their originally wild counterparts. These differences may partially be explained by differences in food quality and availability among the populations. However, there is a growing suspicion that other explanatory factors are also involved. Wild reindeer are more vigilant and show longer fright and flight distances than feral reindeer. Number of animals harvested was 4817, or ca. 20% of the total population in 2005, but varies between 40% in feral reindeer areas to below 20% in some of the "wild" reindeer areas. Causal factors behind this variation include differences in age at maturation, postnatal calf mortality and herd structure. The Norwegian Institute for nature research (NINA) in cooperation with the Directorate for nature management (DN) allocate considerable resources to monitoring 36 wild reindeer herds and pastures, especially winter pastures. A total of 8 wild reindeer areas are monitored annually (the monitoring program was initiated in 1991), recording calf recruitment rates in nursery bands in June/July from aerial photographs and herd composition from ground counts of rutting groups in September/ October. Carcass weights and mandibles are sampled at regular intervals from harvested animals in the same areas in order to investigate reindeer body weight development. The botanical part of the monitoring program is concentrated on renewal growth of lichen in areas under variable reindeer grazing pressure, and annual measurements of radiocesium load in plants and reindeer meat from fall-out areas following the Chernobyl accident in 1986. Reindeer research relating to the wild reindeer herds in southern Norway is mainly conducted by NINA in Trondheim and the Biology Institute, University of Oslo. Most mountain ranges and wild reindeer populations in Norway are experiencing an increase and expansion of human use, including infrastructure such as road and power-lines, and private cabins, tourism/recreation, etc. Present research activities focus on wild reindeer area use, behaviour and activity budgets in selected areas on a 24 hour and a seasonal basis by use of GPS-technology. An important part of the ongoing projects emphasizes a close monitoring and investigation of reindeer behaviour and activity in relation to human activities and infrastructure. Furthermore, development and quality control of methods for measurement of response towards anthropogenic activities and population reproduction and early calf mortality are included in the research activities. Villrein i Norge; Populasjonsøkologi, forvaltning og jakt Abstract in Norwegian / Sammendrag: Villreinen i Norge utgjør i 2005-06 en vinterbestand på ca. 25 000 dyr fordelt på 23 stort sett isolerte villreinområder (kart i appendiks) som jaktelig sett forvaltes enkeltvis og i et samarbeid mellom rettighetshavere og statlige forvaltningsorganer. Presentasjonen gir en historisk fremstilling av villreinforvaltningen i Norge og den forskningsutvikling som ligger bak dagens situasjon. Vi har 3 typer villrein i Norge: (1) den opprinnelige med liten tamreininnblanding karakterisert ved områdene Snøhetta, Rondane og Sølenkletten, (2) villrein med varierende innslag av tamreinpåvirkning (Nordfjella, Hardangervidda, Setesdal-Ryfylke) og (3) villrein med tamreinopphav (dvs. forvillet tamrein; Forolhogna, Ottadalen Nord og Ottadalen Syd, Norefjell-Reinsjøfjell og en rekke mindre områder). Reinens kroppsvekter i kategori 3-områdene er vesentlig høyere enn de i kategori 1 og 2. Forskjeller i beiteforhold områdene i mellom er nok medvirkende årsak, men adferdsundersøkelser som omfatter vaktsomhetsadferd og frykt- og fluktadferd i ulike områder tyder på at vaktsomhet og aktivitetsmønster kan være andre viktige påvirkningsfaktorer. Avkastningen i form av felte dyr var i 2005 ca. 20% av samlet vinterbestand, men varierer mellom 40% i områder der kroppsvektene er store til under 20% der reinen har lavere kroppsvekter. Forklaringsfaktorer omfatter forskjeller knyttet til alder for kjønnsmodning og reproduksjon, postnatal kalvedødlighet og kjønns- og alderssammensetning i de ulike villreinområdene. Norsk villreinforvaltning i regi av Norsk institutt for naturforskning (NINA)/Direktoratet for naturforvaltning (DN) satser store ressurser på overvåkning av villrein og deres beiter, særlig vinterbeiter. Til sammen 7 spesielt utvalgte villreinområder overvåkes årlig (start 1991) med flyfotografering av fostringsflokker i juni/juli for å bestemme kalvetilvekst og bakkeregistreringer om høsten for å bestemme bestandsstruktur. Med jevne mellomrom innsamles også kjever og slaktevekter fra høstjakten for å vurdere reinens kondisjonsutvikling i overvåkningsområdene. I den botaniske del av overvåkningsaktivitetene måles gjenvekst av lav i områder utsatt for vekslende beitepress og radiocesiumbelastningen etter Tsjernobylulykken i 1986 i næringsplanter og i kjøttprøver fra felt villrein i de områdene som ble hardest rammet av nedfall. Villreinforskningen er særlig lokalisert til NINA og Universitetet i Oslo. Forskningsaktivitetene omfatter måling av reinens adferd og aktivitet gjennom døgnet og dyrenes sesongmessige områdebruk i relasjon til menneskelig infrastruktur i utvalgte områder ved hjelp av bl.a. GPS-instrumentering og utvikling og kvalitetskontroll av metodeverktøy til bestemmelse av reproduksjon og tidlig kalvedødlighet.